ANALISIS PEMILIHAN SUPPLIER PACKAGING PADA PT. XYZ DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DAN BEST WORST METHOD (BWM) - Muthia Zenzy Ariani (2022)
Supplier becomes one of the most important parts in a company engaged in the manufacturing industry such as PT. XYZ. PT. XYZ is one of the largest paper industry companies in Indonesia that produces various types of paper. In the procurement process, they often face problems such as product delivery that is not on time, there is damage to the product sent, and suppliers who are not responsive. So that it can cause losses to the company and hinder the movement of goods in the supply chain. The purpose of this study is to determine the order of criteria that influence the selection of suppliers and to find out the best alternative suppliers in the procurement process at PT. XYZ by using the Analytical Hierarchy Process (AHP) and Best Worst Method (BWM). In this case, there are 8 criteria used for supplier assessment. The results obtained from data processing with the AHP method are the price quote criteria that have the highest weight of 0.293, followed by a discount of 0.159, a history of performance of 0.131, on time delivery of 0.103, quality certificates of 0.094, responsiveness of 0.068, and compliance orders of 0.058. Furthermore, data processing using AHP and BWM methods. The final result is Supplier A's Optimal Weight of 0.668, Supplier B of 0, and Supplier C of 0.332. So it can be seen that Supplier A is the best alternative that can be used as a priority supplier to cooperate or carry out a sustainable contract in the packaging procurement process at PT. XYZ. It is expected that the company can implement the results of the assessment of several related suppliers, so that they can establish cooperation or contracts with the best alternative suppliers on an ongoing basis to reduce losses to the company from the impact of problems that often occur.